Higgs amplitude mode in a two-dimensional quantum antiferromagnet near the quantum critical point - Hong, Tao; Matsumoto, Masashige; Qiu, Yiming; Chen, Wangchun; Gentile, Thomas R.; Watson, Shannon; Awwadi, Firas F.; Turnbull, Mark M.; Dissanayake, Sachith E.; Agrawal, Harish; Toft-Petersen, Rasmus; Klemke, Bastian; et al. (Nature, 2017)
Spontaneous symmetry-breaking quantum phase transitions play an essential role in condensed-matter physics(1-3). The collective excitations in the broken-symmetry phase near the quantum critical point can be characterized by fluctuations of phase and amplitude of the order parameter. The phase oscillations correspond to the massless Nambu-Goldstone modes whereas the massive amplitude mode, analogous to the Higgs boson in particle physics(4,5), is prone to decay into a pair of low-energy Nambu-Goldstone modes in low dimensions(2,6,7). Especially, observation of a Higgs amplitude mode in two dimensions is an outstanding experimental challenge. Here, using inelastic neutron scattering and applying the bondoperator theory, we directly and unambiguously identify the Higgs amplitude mode in a two-dimensional S = 1/2 quantum antiferromagnet C9H18N2CuBr4 near a quantum critical point in two dimensions. Owing to an anisotropic energy gap, it kinematically prevents such decay and the Higgs amplitude mode acquires an infinite lifetime.